Effect of Bottom Bracing Configuration on Mid-Span Deflection of Tied Steel Arch Bridge - Faiz Razaan Neema; Dzulkarnain Muhammad Khazruya; Izatullilah Izatullilah; Dzul Fikri Muhammad (Universitas Islam Raden Rahmat, Malang, 2026)
Tied steel arch bridges are commonly used due to their structural efficiency and aesthetic value; however, excessive mid-span deflection remains a critical design issue. While previous studies indicate that bottom bracing can enhance stiffness, the optimization of bracing configurations at the mid-span has not been sufficiently investigated. This study evaluates the influence of different bottom bracing configurations on mid-span deflection in tie-beam steel arch bridges. Numerical analysis based on the finite element method was conducted using SAP2000 v.22 on four bridge models with identical geometry, loading conditions, and a total bottom bracing weight of 10 kg. The bridge span was 4 m with an allowable deflection limit of 5 mm. The results show that all configurations satisfy the deflection criteria, with the X-bracing configuration yielding the smallest mid-span deflection. These findings contribute to the understanding of optimal bottom bracing configurations in steel arch bridge design, supporting efficient structural performance in engineering applications.